Study of a Relationship between the Criteria for Selection of the Transport Technology for the Passengers Carriage using the Dematel Method - Svetla Stoilova (Communications - Scientific letters of the University of Zilina, 2020)
This study defines criteria and sub-criteria for evaluation of the transport technology for carriage of passengers by railway and road transport. The main criteria are divided into four groups: business, environmental, social and technological, named BEST analysis. Twenty-four sub-criteria have been examined. The method of multi-criteria analysis Decision Making Trial and Evaluation Laboratory (DEMATEL) has been applied to analyse importance and the relations between the criteria. Results show that e criteria of the great importance are business group (29.47%) and technological group (27.49%). The sub-criteria: transport costs for fuel (7.83%); ticket price (8.29%); time travel (6.99%); directness (6.47%) and direct operating costs (6.30%) are the most important. The defined criteria and subcriteria can be applied for evaluation, comparison and selection the transportation variant.